Expansive Soil Stabilization Using Mud (Lapindo) and Asphalt Emulsion - Resti Meysita Pramaesti; Syahril; Hendry (Potensi: Jurnal Sipil Politeknik, 2021)
Most of Gedebage area consist of expansive soil and always greatly induce disturbance to structure of foundation. Nature properties of expansive soil is a high plasticity value, low soil shear strength, high swelling, and large potential for shrinkage. One solution for soil improvement is to use an additional material to stabilize this soil. Additional material uses locked emulsion asphalt 8% and mud from Lapindo area in variation of 3%, 6%, 9% and 12%. The results of testing the physical and mechanical properties after stabilization indicates increasing of density value around 68%. Plasticity index tends to decrease until 10% from CBR test. CBR values with curing time of 14 days are 8.1% for unsoaked and by 4.6% for soaked conditions.